Higher Education Institutions and Social Responsibility in the Context of Sustainability - Cantú-Martínez, Pedro César (2013)
This review article explores an issue of vital importance to higher education institutions, that is, social responsibility. The social responsibility approach is back on the table of the environmental crisis and sustainable development debates. This review article explains how higher education institutions, particularly in México, should have a permanent highly relevant qualitative-quantitative development to contextualize the demands of society. It refers to